1983
DOI: 10.1177/030098588302000208
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma in a Phthisical Feline Eye

Abstract: Abstract. Eight years ago a cat sustained injury to the left globe and phthisis bulbi ensued. Two months prior to presentation, a firm intraorbital and periorbital mass developed and enucleation was done; histologic examination revealed osteogenic sarcoma. This is the first histologically documented report of osteosarcoma occurring in association with phthisis bulbi.Intraocular bone formation has been noted in a variety of conditions affecting eyes in man and animals [7,15]. Although intraocular ossification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…coma of the eye, had a reported history of trauma; however, cases of post-traumatic osteosarcoma arising from the eye have been reported in cats. 39 Similarly, 10% of extraskeletal osteosarcomas in human beings develop at a site that has been i~~a d i a t e d . '~,~~ None of our dogs had a history of irradiation, but post-radiation sarcomas have been reported in dog^.^^,^^ Extraskeletal osteosarcomas in dogs are highly malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…coma of the eye, had a reported history of trauma; however, cases of post-traumatic osteosarcoma arising from the eye have been reported in cats. 39 Similarly, 10% of extraskeletal osteosarcomas in human beings develop at a site that has been i~~a d i a t e d . '~,~~ None of our dogs had a history of irradiation, but post-radiation sarcomas have been reported in dog^.^^,^^ Extraskeletal osteosarcomas in dogs are highly malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Long et al [5] reported an 86-year-old woman with extraskeletal osteosarcoma following a 20-year history of phthisis bulbi secondary to multiple ocular procedures and uncontrolled glaucoma. While earlier descriptions of extraskeletal osteosarcoma arising in phthisical eyes in felines have been reported [6][7][8], Long et al's report is the only other example involving a phthisical human eye. Similar to our case, their patient's presentation included pain and proptosis.…”
Section: Discussionmentioning
confidence: 90%
“…The initial case was reported by one of the authors of this paper (DMA and associates) in 1983. 11 The following year, Dubielzig reported 3 cases of lens malignancy in the feline eye following ocular trauma. 12 In a subsequent study, it was established that rupture of the lens capsule was a major risk factor for development of the tumor and, on the basis of the histologic appearance, the name “feline ocular post-traumatic sarcoma” (FOPTS) was suggested.…”
Section: Resultsmentioning
confidence: 99%
“…8–10 More strikingly, malignant tumors of the lens can spontaneously occur in other species of non-human vertebrates. 1118 During the last 25 years, considerable knowledge has accumulated regarding the “regulatory circuits” that must be disrupted in order for a cell to become malignant. The purpose of the present study was to determine in which species and, under what conditions, lens tumors occur by studying human and veterinary pathologic material available to us, combined with a review of the literature.…”
mentioning
confidence: 99%